The Effect of Crossword Media Counseling on the Knowledge of Class X Students in Kota Padang About Obesity and Body Weight - Deni Maisa Putra; Devid Leonard; Muhammad Al-Ashari; Aulia Syahrani (Sustainable Applied Modification Evidence Community (SAMEC), 2024)
Obesity and overweight have rapidly grown as a public health problem worldwide, including in Indonesia. The prevalence of overweight and obesity among Indonesian children and adolescents has also increased significantly in recent years (Maulina, 2022). This suggests that better interventions and prevention are needed to address this issue, especially for students (Susanti & Legal and Public Relations Working Team, 2019). All countries, including Indonesia, face the problem of being overweight, or overweight, and overweight, or obesity. Based on data from the Global Nutrition Report, 10% of the adult population in Indonesia is overweight, and 2% is obese (WHO, 2007). Therefore, this study aims to fill the knowledge gap by investigating the effect of counseling using crossword media on students' knowledge and attitudes about overweight and obesity. This study involved 48 grade X students who were overweight or obese. The sample was drawn from the entire overweight and obese population. Results showed that grade X students in Padang City had significant knowledge about overweight and obesity before and after counseling without using crossword media (p=0.000). In addition, there was a significant difference between students' knowledge on this topic before and after counseling using crossword media (p=0.000). According to the study, the use of crossword media has a significant effect on increasing students' knowledge. Therefore, it is recommended that students continue to use this media in instructional or learning activities at school.